MILESTONES OF PERSONNEL MANAGEMENT SCIENCE IN RUSSIA - Y. Proshina (Вестник университета)
The article below reviews our country staff management art main development stages. Author in details describe pre-Soviet Russia staff management art key features. Soviet Russia positive HR management sides pointed. In addition, these value losses related with market economy transition. Staff management department’s workflow main issues considering for the moment. Author emphasize dedicated HR specialist’s educational programs poor level. Finally, there is modern HR service function list presented. Such a list secure successful enterprises functioning for today.